Design and Construction of Automatic Lighting System Using Microcontroller Based on Wireless Sensor Network - Dali, Sri Wahyuni; Mas'udia, Putri Elfa; Fauzan, Hanif (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
A manual system that can be improved with an automatic system, one of which is the lighting system. The use of lights in the community today is considered not in accordance with their use, often the lights are still on even though they are not used, this is a waste. The type of research used is manufacturing or development research, this research aims to design and build an automatic lighting system using a Wireless Sensor Network (WSN)-based microcontroller that has a problem of wasting electricity in the use of lights. Based on this problem, an implementation of a wireless sensor network using a microcontroller was made to reduce waste in using electricity. The way the system works is that the node device system will send the sensor reading data to the gateway every time there is a change in the data. After the data is received, the gateway is then uploaded to the firebase database first and then accessed on the user's application on the smartphone. The test results show that the system made by both hardware and software is running according to plan with the detection latency of camera one is per 0.233 milliseconds, the detection latency of camera two is per 0.213 milliseconds, the detection latency of camera three is per 0.219 milliseconds, but this latency is highly dependent on the strength of the Wi-Fi signal used. This system is able to reduce the use of electricity by 5 watts, and 7.5 rupiah per hour.